UPAYA PENINGKATAN MUTU PENDIDIKAN TINGGI SERTA IMPLIKASINYA TERHADAP TUGAS DAN PERAN DOSEN - Rizkan Syahbuddin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
National development that  lasts  all the  time,  then the  development of higher education is still prioritized by the government to continue to grow, including the role and  duties of lecturers. Strategy  setting is part  of long-term development. The goal is in the most appropriate way in the future to be able. Improving the quality of higher education can not be separated from the quality of human resources owned. Therefore, improving the quality of the behavior and behavior of lecturers as teachers through education channels and  effective training programs in their  work is needed. With qualified human resources, it is expected that  higher education will become an institution capable of effectively facing the challenges of the future.